2008
DOI: 10.1007/s10867-008-9122-z
|View full text |Cite
|
Sign up to set email alerts
|

Hydration Profiles of Amyloidogenic Molecular Structures

Abstract: Hydration shells of normal proteins display regions of highly structured water as well as patches of less structured bulk-like water. Recent studies suggest that isomers with larger surface densities of patches of bulk-like water have an increased propensity to aggregate. These aggregates are toxic to the cellular environment. Hence, the early detection of these toxic deposits is of paramount medical importance. We show that various morphological states of association of such isomers can be differentiated from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 49 publications
1
16
0
Order By: Relevance
“…Recently, Nucci et al (24) demonstrated that water proton magnetic resonance spectroscopy can resolve dynamics of water at the surface of proteins. Moreover, the results (24) suggest that water-rearrangement processes in the next hydration layers closely correlate with hydration properties of specific water patches on the protein surface (25), which was also predicted by computer simulations (22,26,27). The work by Nucci et al (24) supports also the idea (21)(22)(23) that the magnetic relaxation of water in the hydration shells of proteins is a valuable tool to probe pathogenic proteins associated with many diseases.…”
Section: Introductionmentioning
confidence: 58%
See 3 more Smart Citations
“…Recently, Nucci et al (24) demonstrated that water proton magnetic resonance spectroscopy can resolve dynamics of water at the surface of proteins. Moreover, the results (24) suggest that water-rearrangement processes in the next hydration layers closely correlate with hydration properties of specific water patches on the protein surface (25), which was also predicted by computer simulations (22,26,27). The work by Nucci et al (24) supports also the idea (21)(22)(23) that the magnetic relaxation of water in the hydration shells of proteins is a valuable tool to probe pathogenic proteins associated with many diseases.…”
Section: Introductionmentioning
confidence: 58%
“…Water molecules at the interface with amyloidogenic peptides undergo considerable reorganization during the aggregation process (11,12,(21)(22)(23)31,32). As the peptides associate forming oligomers and fibrils, their hydrophobic patches are buried inside the newly formed amyloidogenic assembly.…”
Section: Theoreticalmentioning
confidence: 99%
See 2 more Smart Citations
“…The latter have the advantage that they can be conducted in vivo (Kasthurirangan et al, 2008) but are limited in that refractive index is calculated from protein concentrations derived from transverse relaxation times of water protons. This has relevance to soluble protein homogenates (Hills et al, 1989) but takes no account of insoluble protein or the fact that water in the intact lens exist in free and bound states and that these produce differences in transverse relaxation times (Despa et al, 2008). These factors are particularly significant for any conclusions about age-related changes in refractive index given that with age there is an increase in both insoluble protein (Pirie, 1968;Satoh, 1972;Lahm et al, 1985) and free water (Lahm et al, 1985;Bettelheim et al, 2002;Heys et al, 2008).…”
Section: Discussionmentioning
confidence: 99%